2022
DOI: 10.1016/j.jbc.2021.101496
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of DBC1 with polyoma small T antigen promotes its degradation and negatively regulates tumorigenesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…To validate that this interaction of PP2A subunits is specific to PCTAIRE1, we also probed DBC1 (also known as CCAR2) and SIRT1 in the same experiment. This was relevant, as our other studies have shown that PolST interacts with DBC1, which consequently affects its association with SIRT1 deacetylase ( Sarwar et al, 2022 ). Our results did not show any such interaction between PCTAIRE1 and these proteins, thus confirming that the interaction between PCTAIRE1 and PP2A subunits is specific.…”
Section: Resultsmentioning
confidence: 84%
“…To validate that this interaction of PP2A subunits is specific to PCTAIRE1, we also probed DBC1 (also known as CCAR2) and SIRT1 in the same experiment. This was relevant, as our other studies have shown that PolST interacts with DBC1, which consequently affects its association with SIRT1 deacetylase ( Sarwar et al, 2022 ). Our results did not show any such interaction between PCTAIRE1 and these proteins, thus confirming that the interaction between PCTAIRE1 and PP2A subunits is specific.…”
Section: Resultsmentioning
confidence: 84%
“…The LKB1‐AMP kinase axis negatively regulates this pathway through the phosphorylation and activation of TSC1/2 complex (Inoki et al 2003). In addition, we have also found out that AKT1 and LKB1 regulate protein levels of some proteins (e.g DBC1/CCAR2 and PCTAIRE1/CDK16) in contrasting ways (Gillani et al 2022; Sarwar et al 2022). We therefore tested the effect of LKB1 on lipin‐1 protein levels.…”
Section: Resultsmentioning
confidence: 97%
“…Our study demonstrates that CCAR2 is one of the regulatory proteins for mitotic progression. Sarwar et al showed that CCAR2 is localized to nucleoplasm during interphase, to spindle poles during prometaphase and metaphase, to midzone during anaphase, and midbody during telophase and cytokinesis [ 18 ]. However, we observed that CCAR2 is leaked to cytoplasmic region after nuclear envelope breakdown and re-localized in nucleoplasm after nuclear membrane assembly during mitotic phase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CCAR2 is required for the expression of a subset of cell cycle-regulated genes in human squamous cell carcinoma cells [ 17 ]. A recent report also showed that CCAR2 is required for exit from polyoma small T (PyST)-induced mitotic arrest [ 18 ]. Although a role for CCAR2 in regulating mitosis has been suggested, no study has reported the direct role of CCAR2 in mitosis.…”
Section: Introductionmentioning
confidence: 99%